Current status and new norms of nitrogen nutrition for grapevine (Vitis vinifera) - Bhargava, B S; Raghupathi, H B (The Indian Journal of Agricultural Sciences, 2012)
A survey was conducted in Andhra Pradesh, Maharashtra and Karnataka. to study the nutritional status of nitrogen in grapevine (Vuis vinifera L.) and soils of vineyards. The new norms for classification of N status in plants and soils were developed using diagnosis and recommendation integrated system (DRIS). The optimum N in petiole was 0.5 I .25% in I Anab-e-Shahi’ and 0.87-1.61% in ’Thompson Seedless’. The optimum status of available N in soil of â€˜Anab-e-Shahi’ was 179-628 ppm and of ’Thompson Seedless 103-262 ppm. For ’Anab-e-Shahi’ the optimum dose of N was 1.09-3.48 and 1.16-3.75 kg/plant/year for Andhra Pradesh and Karnataka respectively, and for ’Thompson Seedless’ was 0.28-0.74, 0.58-1.54 and 0.35-0.93 kg/plant/year for Andhra Pradesh, Maharashtra and Karnataka respectively.